A Model of the Costs of Community and Nosocomial Pediatric Respiratory Syncytial Virus Infections in Canadian Hospitals - Philip Jacobs; Douglas Lier; Katherine Gooch; Katharina Buesch; Michelle Lorimer; Ian Mitchell (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND: Approximately one in 10 hospitalized patients will acquire a nosocomial infection (NI) after admission to hospital, of which 71% are due to respiratory viruses, including the respiratory syncytial virus (RSV). NIs are concerning and lead to prolonged hospitalizations. The economics of NIs are typically described in generalized terms and specific cost data are lacking.